Effectiveness of Peroxyacetic Acid as Disinfectant to Physico-chemical, Microbial and Organoleptic Characteristics of Fresh Pangasius Fillet during Chilling Storage - Minh Phuoc Nguyen (Journal of Global Pharma Technology, 2016)
Pangasius fillet is a good source of amino acids, low residue levels of heavy metals and polychlorinated biphenyls, high amounts of saturated fatty acids, low amounts of polyunsaturated fatty acids, low cholesterol levels. However, it is highly perishable.  During the processing of Pangasius fillets, washing could reduce the microbial loads on the fish fillets as much as possible.  Objective of this study focused on the efficacy of different concentrations of peroxyacetic acid (PAA) to the firmness (N), peroxide value (meq/kg), total plate count (cfu/g), sensory score of fresh Pangasius fillet during 20 days of preservation at cooling temperature. Our results showed that 75ppm PAA was appropriate to maintain physico-chemical, microbial and sensory characteristics of fresh Pangasius fillet during storage.Keywords: Pangasius fillet, Peroxyacetic, Firmness, Peroxide value, Total plate count, Sensory score.